1997
DOI: 10.1042/bj3260903
|View full text |Cite
|
Sign up to set email alerts
|

Mucus glycoproteins from pig gastric mucosa: identification of different mucin populations from the surface epithelium

Abstract: Pig gastric mucins were isolated from the surface epithelium of the cardiac region, corpus and antrum using density-gradient centrifugation after extraction in 6 M guanidinium chloride. In CsCl/0.5 M guanidinium chloride, mucins solubilized from the cardiac region appeared as a broad unimodal band at 1.52 g/ml whereas those from the corpus and antrum occurred as high- and low-density populations at 1.50 and 1.45 g/ml respectively. High-iron diamine reacted more strongly with the cardiac mucins and the high-den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
60
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(66 citation statements)
references
References 33 publications
6
60
0
Order By: Relevance
“…The bound sulfate level in PGM is approximately fourfold lower than that for MUC5B ( Fig. 1) but the macromolecular composition of commercial PGM has not been defined and there are considerable differences in size, density, glycosylation and sulfation of mucin preparations isolated from different areas of the pig gastric mucosa (Nordman et al, 1997). Commercial preparations are, therefore, likely to be heterogeneous mixtures and may contain not only sulfated mucin but also other sulfated glycoconjugates.…”
Section: Discussionmentioning
confidence: 99%
“…The bound sulfate level in PGM is approximately fourfold lower than that for MUC5B ( Fig. 1) but the macromolecular composition of commercial PGM has not been defined and there are considerable differences in size, density, glycosylation and sulfation of mucin preparations isolated from different areas of the pig gastric mucosa (Nordman et al, 1997). Commercial preparations are, therefore, likely to be heterogeneous mixtures and may contain not only sulfated mucin but also other sulfated glycoconjugates.…”
Section: Discussionmentioning
confidence: 99%
“…This attraction has been attributed to a charge interaction between the positive amino groups and the sialic acid or sulphate residues on the mucosal glycoproteins. Structural studies have indicated that the negative charge on PGM is thought to be attributed mostly to the amount of sulphated O-linked oligosaccharide residues in the glycosylated region and not to the amount of sialic acid present [22].…”
Section: Control Surfacesmentioning
confidence: 99%
“…SNA binds sialic acid residues, [ 44 ] which are rare in the pig gastric mucin used for this study. [ 45 ] As a consequence, SNA binding to mucin is weak ( Figure S7, Supporting Information), and there was no signifi cant impact of SNA-PEG on hydration ( p = 0.151), confi rming that binding of the PEG to the pApoMucin coating is necessary to restore hydration. If the hydration state of deglycosylated mucins can be brought back to that of intact mucins, then the lubricating abilities of those "repaired mucins" might also approximate those of fully glycosylated mucins.…”
Section: Lectin-peg Recovers Hydration and Lubrication Of Deglycosylamentioning
confidence: 99%
“…The protein solutions were pumped to fi ll the reservoir above the crystal surface, and then the fl ow was stopped to allow the coating to form. The crystal vibration was followed at its fundamental frequency (5 MHz) and six overtones (15,25,35,45,55, and 65 MHz). Changes in the resonance frequencies and in dissipation of the vibration once the excitation was stopped were followed at the seven frequencies.…”
Section: Methodsmentioning
confidence: 99%